(untitled) (Advances in Applied Biological Research, 2026)
The present study was conducted to document the traditional knowledge and utilization of plant resources by the Gond tribe inhabiting Chiharitola village of Mohla-Manpur-Chowki district, Chhattisgarh, India. The study aimed to assess the knowledge and use of local plant species in relation to livelihood, healthcare, food, rituals, handicrafts, and other socio-cultural practices. Field investigations were carried out from January to March 2024 using ethnobotanical survey methods, including structured questionnaires, interviews with knowledgeable elders, village leaders (Gayta), field observations, group discussions, and plant specimen documentation. Plant species were identified using standard floristic literature and verified with the assistance of local informants. The investigation documented a total of 50 plant species belonging to 20 families. Among these, 20 species were utilized for livelihood security and non-timber forest products, 8 species for ritual and cultural ceremonies, 8 species for traditional medicinal purposes, 5 species as cultivated crops, 4 species as wild edible resources, 3 species as host plants for lac production, 3 species for gum collection, and 2 species for residential construction. The families Fabaceae, Poaceae, Combretaceae, Sapotaceae, and Anacardiaceae were found to be the most dominant and economically important. Various plant parts, including fruits, seeds, leaves, flowers, stems, bark, and tubers, were used for food, medicine, handicrafts, construction, and income generation. The study revealed that non-timber forest products such as mahua (Madhuca longifolia), tamarind (Tamarindus indica), char (Buchanania lanzan), tendu (Diospyros melanoxylon), honey, lac, and gums play a significant role in supporting the livelihoods of tribal households. Several plant species were also found to be closely associated with traditional rituals, including birth ceremonies, marriages, Nawakhai celebrations, and funeral rites. Medicinal plants such as Azadirachta indica, Tinospora cordifolia, Ocimum sanctum, and Andrographis paniculata continue to serve as important healthcare resources within the community. The findings highlight the rich ethnobotanical knowledge of the Gond tribe and demonstrate the crucial role of plant resources in sustaining their socio-economic and cultural life. Documentation and conservation of this indigenous knowledge are essential for promoting biodiversity conservation, sustainable resource management, and the preservation of traditional cultural heritage for future generations.